PERTIMBANGAN HAKIM ATAS GUGATAN PENGGUGAT TIDAK DAPAT DITERIMA DALAM PERKARA PERCERAIAN - Ndruru, Antonius; Laia, Laka Dodo (JURNAL PANAH KEADILAN, 2024)
Divorce is a manifestation of the failure of the goal of marriage to form a happy and eternal family. One of the divorce lawsuits that has been decided by the district court and has permanent legal force is decision number 41/Pdt.G/2021/PN Gst. In this decision, the judge handed down the decision "the plaintiff's claim cannot be accepted" because the reason for the dissolution of the marriage stated by the plaintiff did not meet the requirements for dissolution of the marriage. Therefore, this research aims to find out and analyze the judge's considerations regarding the decision that the plaintiff's lawsuit cannot be accepted in a divorce case (study decision number 41/Pdt.G/2021/PN Gst). The type of research used in this research is normative legal research using secondary data and using the statutory regulatory approach, case approach and analytical approach, as well as using qualitative data analysis. Based on the research findings and discussion, the author concludes that the judge's basic consideration of the plaintiff's claim cannot be accepted in a divorce case (study decision number 41/Pdt.G/2021/PN Gst) with the decision not being accepted because the panel of judges focuses on the reasons - the reasons for divorce as intended in Article 19 letter b of the PP Implementing the Law on Marriage. The author suggests that everyone who files a lawsuit for divorce must pay attention to the reasons for divorce that have been specified in Article 19 letter b of the PP Implementing the Law on Marriage.